Differences in selected fitness, tennis skills and functional movement following functional movement training program among young male Chinese tennis players - Xiao, Wensheng (2022)
The purpose of this research was to evaluate the effect of a 12-week functional training intervention on selected fitness, tennis skills, and functional movement among Chinese young male tennis players. The group (centers) was used as the unit of randomization, and the training bases of young tennis players were selected from 11 representative teams using the Lottery Method and the same method was used to select the functional training group (FTG) and control group (CTG). Forty-four eligible participants were recruited from both training sites in Zhejiang provinces. Subjects were between the ages of 14-18 years. A Cluster Randomized Controlled Trial study was conducted. Both groups performed for 60 minutes, three times a week (36 sessions). The fitness and tennis skills test procedures followed the International Tennis Federation's recommend test protocol, as well as the functional movement test procedures, following the functional movement screen test protocol. Data collection procedures for the control group (CTG) were collected the same as for the functional training group (FTG). Additionally, those test protocols were used to assess changes in the dependent variables that resulted from intervention at zero, six, and 12 weeks. The Generalized Estimating Equations determined differences between and within the group. The hypotheses of the thesis received significant support. Within-group effects showed significant differences between FTG and CTG for three times time fitness and skills variables (p<0.05) except for volley depth between posttest 1 and posttest 2 was not statistically significant in CTG (p>0.05). Additionally, for FTG, except for deep squat, in-line lunge, active straight leg raise, trunk stability push-up, and rotary stability was no statistical significance between pretest and posttest 1 (p>0.05), for other functional movement variables, the results were significant (p<0.05). In the CTG, the results were not significant for other functional movement variables (p>0.05), except for the total score, which was signed between pretest and post-test 2, hurdle step and shoulder mobility were significant between both post-tests. Between-group effects showed that all dependent variables (fitness, skills, and functional movement) were not statistically significant at the pretest (p>0.05). There was a statistically significant difference in fitness (wall squat test, left), functional movement (deep squat, trunk stability push-up, rotary stability) at posttest 1 (p<0.05), while tennis skills variables had statistically significant differences at posttest 1 (p<0.05). Additionally, all dependent variables had significant differences at posttest 2 (p<0.05), except for the speed variable (p>0.05). The results showed that functional training is more effective than standard training in improving fitness, skills, and functional movement in young tennis players. For skills training, six weeks of functional training had a more significant effect than standard training. This improvement is mainly due to the specific functional training principle that stimulates and facilitates the improvement of the target movement. Therefore, it can be used to replace standard training, as it promotes better improvement in fitness, skills, and functional movement of young male tennis players. Future research is recommended to explore functional training in other sports, and other genders while observing the effects on fitness and skill parameters.